Health Providers' Advising on Symptom Management for Upper Respiratory Tract Infections: Does Elaboration of Reasoning Influence Outcomes Relevant to Antibiotic Stewardship?. (June 2020) - Foley, Kasey A.; MacGeorge, Erina L.; Brinker, David L.; Li, Yuwei; Zhou, Yanmengqian
Antibiotic-resistant infections, fueled by unwarranted antibiotic prescribing, are an increasing threat to public health. Reducing overprescribing and promoting antibiotic stewardship requires managing patient expectations for and understanding about the utility of antibiotics. One hotspot for overprescribing is upper respiratory tract infections, for which the best treatment is often non-antibiotic symptom management behaviors. Guided by advice response theory, the current study examines how providers' reason-giving for symptom management advice affected perceptions of advice quality, efficacy for symptom monitoring and management, and satisfaction with care for patients who were not prescribed antibiotics for their upper respiratory tract infections. Transcribed medical visits were coded for symptom management advice reason-giving and patients completed post-visit surveys. Greater provider elaboration about instruction was independently and positively associated with evaluations of advice quality. Results also indicate several significant interactions between types of reason-giving. Implications of these findings for advice theory and clinical practice are addressed in the discussion.